A comparison of interlibrary loan requests received by the National Library of Medicine: 1959 and 1984. - Lacroix, E M (1987)
In 1962, an analysis of interlibrary loan requests for serials filled by NLM in 1959 was published. In the twenty-five years following 1959, important changes occurred in the biomedical library community, which had a significant impact on interlibrary loan activities, including the development of MEDLARS and online searching, the Regional Medical Library (RML) network, and union listing for serials. To describe NLM's current interlibrary loan request traffic for serials and to identify any significant changes in traffic between 1959 and 1984, a comparative analysis of 1984 serial loan requests was performed, primarily by manipulation of automated request records. The changes in request traffic strongly suggest that the efforts to strengthen regional document delivery through the RML program have been successful and that NLM's collection is now used primarily as a last resort.